The Influence of Political Connections, Related-Party Transactions, and Corporate Governance on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange - Nashir, Muhammad; A, Nuraini; Priantana, Riha Dedi (Publikasi Indonesia, 2023)
This study aims to examine the influence of political connections, related-party transactions, and corporate governance on tax avoidance. The sample for this research consists of manufacturing companies listed on the Indonesia Stock Exchange during the period of 2014-2019. The sample was selected using purposive sampling technique, resulting in 25 companies. The analytical technique employed in this research is panel data regression analysis using Eviews version 10 software. The research findings indicate that political connections, related-party transactions, the proportion of independent commissioners on the board, audit quality, and the audit committee have a significant influence on tax avoidance in Indonesian manufacturing companies.